"But I'm not going to be a mental health nurse": nursing students' perceptions of the influence of experts by experience on their attitudes to mental health nursing. (3rd September 2021) - Happell, Brenda; Waks, Shifra; Bocking, Julia; Horgan, Aine; Manning, Fionnuala; Greaney, Sonya; Goodwin, John; Scholz, Brett; van der Vaart, Kornelis Jan; Allon, Jerry; Hals, Elisabeth; Granerud, Arild; et al.
Abstract: Background: Mental health nursing skills and knowledge are vital for the provision of high-quality healthcare across all settings. Negative attitudes of nurses, towards both mental illness and mental health nursing as a profession, limit recognition of the value of these skills and knowledge. Experts by Experience have a significant role in enhancing mental health nursing education. The impact of this involvement on attitudes to mental health nursing has not been well researched. Aim: To explore the impact of Expert by Experience-led teaching on students' perceptions of mental health nursing. Methods: Qualitative exploratory study involving focus groups with nursing students from five European countries and Australia. Results: Following Expert by Experience-led teaching, participants described more positive views towards mental health nursing skills and knowledge in three main ways: learning that mental health is everywhere, becoming better practitioners, and better appreciation of mental health nursing. Conclusions: Experts by experience contribute to promoting positive attitudinal change in nursing students towards mental health nursing skills and knowledge. Attitudinal change is essential for the provision of high-quality mental health care in specialist mental health services and throughout the healthcare sector.